The Impact of Root-Derived Resources on Forest Soil Invertebrates Depends on Body Size and Trophic Position - Bluhm, Sarah L.; Eitzinger, Bernhard; Bluhm, Christian; Ferlian, Olga; Heidemann, Kerstin; Ciobanu, Marcel; Maraun, Mark; Scheu, Stefan (Frontiers in Forests and Global Change, 2021)
Forest soil food webs have been assumed to be fueled substantially by root-derived resources. However, until today the flux of root-derived resources into soil animals has been investigated virtually exclusively using isotope labeling experiments, whereas studies on the consequences of disrupting the flux of root-derived resources into the soil animal food web are scarce. We here investigated the importance of root-derived resources for a wide range of soil animals by interrupting the resource flux into the soil of different forest types in Central Europe using a trenching experiment. We recorded the abundance of soil animal taxa varying in body size (micro-, meso-, and macrofauna) 1 and 3 years after root trenching, and quantified changes in biomass, species composition, and trophic shift using stable isotopes and NLFA analysis. Among the microfauna groups studied (trophic groups of Nematoda) only the abundance of plant feeding nematodes showed a trend in being decreased by -58% due to root trenching. Major soil mesofauna groups, including Collembola and Oribatida, suffered to a similar extent from root trenching with their abundance and biomass being reduced by about 30–40%. The soil macrofauna groups studied (Diplopoda, Isopoda, Chilopoda, Araneae, Coleoptera) generally were only little affected by root trenching suggesting that they rely less on root-derived resources than micro- and in particular mesofauna. Notably, the community structure of micro-, meso-, and macrofauna was not affected by root trenching. Further, we observed trophic shifts only in 2 out of 10 investigated species with the shifts generally being only minor. The results indicate that soil animal communities are markedly resilient to deprivation of root-derived resources suggesting that links to root-derived resources are non-specific. However, this resilience appears to vary with body size, with mesofauna including both decomposers as well as predators being more sensitive to the deprivation of root-derived resources than microfauna (except for root feeders) and macrofauna. Overall, this suggests that body size constrains the channeling of energy through soil food webs, with root-derived resources in temperate forests being channeled predominantly via soil taxa of intermediate size, i.e., mesofauna.